Relative abundance, population structure, habitat preferences and activity patterns of Tapirus bairdii (Perissodactyla: Tapiridae), in Chimalapas forest, Oaxaca, Mexico - Lira-Torres, Iván; Briones-Salas, Miguel; Sánchez-Rojas, Gerardo (Revista de Biología Tropical, 2014)
Baird’s tapir (Tapirus bairdii) is endangered primarily because of habitat loss and fragmentation, and overhunting throughout its distribution range. One of the priority land areas for the conservation of this species is the Northern part of its range in the Chimalapas forest, Oaxaca. The aim of this research was to determine the relative abundance, population structure, habitat preferences and activity patterns of Baird´s tapir (Tapirus bairdii) in the Chimalapas forest, Oaxaca, Mexico, through the non-invasive technique of camera-trap sampling. A total of five sampling sessions were undertaken among 2009-2013, and used a total of 30 camera-traps in each period. The determinant factor of the sampling design was the hunting between two study areas. A total sampling effort of 9 000 trap-days allowed to estimate an index of relative abundance (IRA) of 6.77 tapir photographs/1 000 trap-days (n=61). IRA varied significantly between sampling stations (Mann-Whitney, p<0.01). The frequency of Baird´s tapir photos was higher in the dry season in tropical rain forest without hunting (x², p<0.5). In the rainy season, the tropical rain forest and secondary vegetation habitats showed higher photo frequency than expected from random (x², p<0.5). Considering population structure, a 95.08% of adult animals was obtained in photographic records (n=58). Three types of activity pattern were observed, with more nocturnal records (88.33%; Kruskal-Wallis, p<0.05). The Chimalapas forest appears to be the second most important terrestrial priority ecoregion, just after the Mayan Forest (Campeche, Chiapas, Quintana Roo), for the conservation of tapir populations, not only for Mexico but also for Central America.